ANALYZING TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION - Suminar Ratnasari; Asep Suparman; Muhammad Soni (IPI Garut Press, 2023)
This study focuses on the teachers’ strategies in teaching reading comprehension. The objective of the research is to find out teachers’ strategies in teaching reading comprehension. To reach this objective, this study used qualitative method and case study design for investigating and analyzing the natural situation focused on teachers’ strategies. To collect the data, this study used participants who involved in this study were three teachers in one of senior high schools in Garut. The result showed that the teachers used different strategies in teaching reading comprehension. The strategies are memorizing, question and answer relationship, silent reading, game, discussion, and reading aloud. Hopefully, this study may portray a clear explanation for readers about teacher’s strategies in teaching reading comprehension.